Shale Gas in Poland. Environmental Risk or Prospect for Independence from Foreign Supplies? (Economic and Political Thought, 2012)
The article is aimed at presenting the topic of shale gas in Poland – benefitsand threats connected with its extraction as well as opinions for andagainst expressed by politicians and social activists within a discussion of thetopic. The method used in the article is a case study. Such a form of analysismakes it possible to show various attitudes (of national and foreign parties)regarding extraction of this gas. The aim of this case study is to show not onlyideas worth implementing but also potential mistakes that must be avoided.The shale gas case study lets the author draw conclusions what the reasonsand results of the process are and shows political, economic, technical andsocial conditions connected with shale gas. The discussion of the analyzedtopic results in a short description of the course of work on shale gas extractionand an answer to the question whether it is worth extracting. The conclusionsdrawn after the research in the field suggest that shale gas creates anopportunity to become independent of foreign supply of energy resources.